Kompetensi Guru: Metode Praktik dalam Pembelajaran IPA - Maya Agustina; Havea Juliar Apko (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2021)
This study aims to determine the science teacher of elementary school perceptions in learning science with practical methods. Research carried out by the method blending, mixing qualitative and quantitative. The subjects of the study were Science Teacher and head of MIN (elementary school) Aceh Jaya District. The instrument used was in the form of a teacher's perception questionnaire which was arranged based on a Likert scale and a list of interview questions. The results showed that the perception of teachers in â€œvery goodâ€ category was 92% and the remaining 8% were in the â€œquite goodâ€ category. The result of the interviews showed that the teachers of MIN (elementary school) already understood the importance of learning science with practical methods, but the inadequate facilities and infrastructure caused practicum in science teaching to be rarely carried out.